Struktur Teks Cerita Fantasi Karya Peserta Didik Kelas VII SMPN 1 Kandat Berdasarkan Gaya Belajar - Maidah, Binti Ngafifatul; Zulaeha, Ida; Wagiran, Wagiran (ppjbsip, 2025)
The structure of fantasy story text is an important element as an idea construction that reflects the author's way of thinking. This study aims to describe the structure of fantasy story texts written by students based on visual, auditory, and kinesthetic learning styles. This study is a qualitative study with a descriptive method. The research data are in the form of words that describe the structure of fantasy story texts sourced from grade VII students of SMPN 1 Kandat who have visual, auditory, and kinesthetic learning styles. The determination of research subjects used purposive sampling. The number of subjects in the study was six students with two students for each learning style. Data collection techniques were carried out through documentation with data analysis table instruments. The analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the study show that fantasy story texts written by students of SMPN 1 Kandat, both visual, auditory, and kinesthetic learning styles, have orientation, complication, and resolution structures. Differences in each learning style are shown in the accuracy of the arrangement and variations in the pattern of structure development. Abstrak Struktur teks cerita fantasi merupakan elemen penting sebagai konstruksi ide yang mencerminkan cara berpikir penulis. Penelitian ini bertujuan untuk mendeskripsikan struktur teks cerita fantasi karya peserta didik berdasarkan gaya belajar visual, auditori, dan kinestetik. Penelitian ini merupakan studi kualitatif dengan metode deskriptif. Data penelitian berupa kata-kata yang mengambarkan struktur teks cerita fantasi yang bersumber dari peserta didik kelas VII SMPN 1 Kandat yang memiliki gaya belajar visual, auditori, dan kinestetik. Penentuan subjek penelitian mengggunakan purposive sampling. Jumlah subjek dalam penelitian yaitu enam peserta didik dengan masing-masing gaya belajar dua peserta didik. Teknik pengumpulan data dilakukan secara dokumentasi dengan instrumen tabel analisis data. Teknik analisis yang digunakan yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa teks cerita fantasi karya peserta didik SMPN 1 Kandat baik gaya belajar visual, auditori, dan kinestetik memiliki struktur orientasi, komplikasi, dan resolusi. Perbedaan pada masing-masing gaya belajar ditunjukkan pada ketepatan penyusunan dan variasi pola pengembangan struktur.